Kyphoplastie kombiniert mit intraoperativer Radiotherapie (Kypho-IORT): Therapiealternative für den oligometastasierten Patienten mit Wirbelsäulenmetastasen = Kyphoplasty combined with intraoperative radiotherapy (Kypho-IORT) : alternative therapy for patients with oligometastatic spinal metastases - Bludau, Frederic; Reis, Tina; Schneider, Frank; Clausen, Sven; Wenz, Frederik; Obertacke, Udo (Der Radiologe, 2015)
BackgroundDue to a more effective systemic therapy the survival of patients suffering from malignant tumors has been significantly improved but a longer life span is often associated with a higher incidence of osseous metastases. The majority of these metastases are localized in the spine causing pain, instability and neurological impairments. The interdisciplinary management of spinal metastases previously consisted of stabilization followed by fractionated external body radiation therapy. A reduction in procedural severity and morbidity as well as consideration of self-sufficiency and hospitalization time are important target parameters for these palliative patients.Method and resultsKyphoplasty combined with intraoperative radiotherapy (Kypho-IORT) is one of several modern treatment options, which involves a minimally invasive procedure with local high-dose transpedicular irradiation of the spine with low-energy (50 kV) X-rays. Immediately following irradiation, stabilization of the spine is carried out using kyphoplasty via the same access route so that a single stage procedure with excellent pain reduction and good local tumor control can be achieved. This article presents clinical data for this procedure and the different fields of indications are critically reviewed and compared to other therapy options. Methodological improvements and options for further individualization of therapy are demonstrated.ConclusionThe Kypho-IORT procedure is a safe, feasible and beneficial modern treatment option for instant stabilization and local tumor control in patients with spinal metastases. More than 100 operations have been successfully performed so that the method can be deemed suitable for inclusion in the clinical routine. A phase II dose escalation study has now been completed and submitted for publication and a 2-arm non-inferiority trial (phase III study) for comparison with conventional irradiation is in progress.